The degree of intratumor mutational heterogeneity varies by primary tumor sub-site - Ledgerwood, L. G.; Kumar, D.; Eterovic, A. K.; Wick, J.; Chen, K.; Zhao, H.; Tazi, Loubna; Manna, P.; Kerley, S.; Joshi, R.; Wang, L.; Chiosea, S. I.; et al. (My University, 2016)
In an era where mutational profiles inform treatment options, it is critical to know the extent to which tumor biopsies represent the molecular profile of the primary and metastatic tumor. Head and neck squamous cell carcinoma (HNSCC) arise primarily in the mucosal lining of oral cavity and oropharynx. Despite aggressive therapy the 5-year survival rate is at 50%. The primary objective of this study is to characterize the degree of intratumor mutational heterogeneity in HNSCC. We used multi-region sequencing of paired primary and metastatic tumor DNA of 24 spatially distinct samples from seven patients with HNSCC of larynx, floor of the mouth (FOM) or oral tongue. Full length, in-depth sequencing of 202 genes implicated in cancer was carried out. Larynx and FOM tumors had more than 69.2% unique SNVs between the paired primary and metastatic lesions. In contrast, the oral tongue HNSCC had only 33.3% unique SNVs across multiple sites. In addition, HNSCC of the oral tongue had fewer mutations than larynx and FOM tumors. These findings were validated on the Affymetrix whole genome 6.0 array platform and were consistent with data from The Cancer Genome Atlas (TCGA). This is the first report demonstrating differences in mutational heterogeneity varying by subsite in HNSCC. The heterogeneity within laryngeal tumor specimens may lead to an underestimation of the genetic abnormalities within tumors and may foster resistance to standard treatment protocols. These findings are relevant to investigators and clinicians developing personalized cancer treatments based on identification of specific mutations in tumor biopsies.
Citation: Ledgerwood, L. G., Kumar, D., Eterovic, A. K., Wick, J., Chen, K., Zhao, H., . . . Thomas, S. M. (2016). The degree of intratumor mutational heterogeneity varies by primary tumor sub-site. Oncotarget, 7(19), 27185-27198. doi:10.18632/oncotarget.8448
Additional Authors: Chien, J.;Mills, G. B.;Grandis, J. R.;Thomas, S. M.
Keywords: Deep Sequencing; Hnscc; Hpv; Intratumor Heterogeneity; Mutation